Characteristic of Demography, Economics Factors and Poverty in Gunung Kidul Regency - Suripto, Suripto (Economic Journal of Emerging Markets, 2011)
This paper aims to analyze the determinants of poverty in Gunungkidul Regency in 2006. It analyses SUSENAS data using the logit model with the estimation method of Maximum Likelihood Estimator (MLE). The variables included in the model are the characteristics of demography, economic factors, residential region and business loan. The result shows that poverty in Gunungkidul Regency is associated with residential region, household size, level of employment in agricultural sector, level of education, and the age of household’s head. It also shows that household size is the main source of poverty. In addition, business loan is of important determinant factors in poverty reduction. Keywords: demography, poverty, household size, business loan